Comparison of Advantages of Radially Adjustable Bogie with Conventional Bogie with Regard to New and Worn Transverse Profiles of Rail Head (Current Problems in Rail Vehicles, 2021)
The article focuses on a comparison of running characteristics of rail freight bogies when negotiating curves of small radiuses. The conventional bogie Y25 and the bogie with radially adjustable wheelsets TVP-NG2 are compared. Emphasis was placed on effect of used rail head profile and also on rail head wear effect upon running and operational characteristics of the bogies.
Keywords: radially adjustable bogie; rail profile; curves of small radiuses; transverse wheel forces